The effects of different factors on the removal mechanism of Pb(ii) by biochar-supported carbon nanotube composites. Issue 10 (5th February 2020) - Yang, Yuewei; Sun, Fengfei; Li, Jing; Chen, Junfeng; Tang, Meizhen
Abstract : In this study, biochar and biochar-supported nanocomposites were prepared through the slow pyrolysis of chestnut shells pre-treated with CNTs, and the effects of different factors on the sorption of Pb(ii ) on biochar samples were investigated. Abstract : Herein, biochar-supported nanomaterials were synthesized using a mixture of chestnut shells and carbon nanotubes via slow pyrolysis at 600 °C for 1 h. Then, the adsorption ability of chestnut shell-carbon nanotubes (CS-CNTs) towards the removal of aqueous Pb(ii ) was tested. The removal capacity of Pb(ii ) by CS-CNT was 1641 mg g −1, which was significantly higher than that by the biochar of chestnut shells (CSs) (1568 mg g −1 ), which demonstrated that the sorption capacity could be improved by the carbon nanotubes. The factors studied here indicated that the adsorption was rapid in the initial 15 min under the conditions of the Pb(ii ) concentration of 50 mg L −1 and the pH value of 5, and the values reached 1417 mg g −1 and 1584 mg g −1 . The adsorption rate and capacity increased on increasing the concentration of NaCl. The sorption reaction was consistent with the Langmuir model, indicating a mono-layer adsorption behavior. The adsorption process can also be defined via the pseudo-second-order model, suggesting that the adsorption of Pb(ii ) might be controlled by chemisorption. After carrying out four cycles of adsorption–desorption experiments, the adsorption rates of CS and CS-CNT remained at 82.92% and 88.91%, respectively, indicating that the biochar samples had stable and excellent sorption ability for heavy metals and huge application value. Thus, this study would provide a promising sorbent for the treatment and remediation of metal contaminants.